cut to fit the tool-spun course. - Montfort, Nick; Strickland, Stephanie (DHQ: Digital Humanities Quarterly, 2013)
"cut to fit the toolspun course" includes a new gloss by the authors on the original JavaScript code. The code was originally published with some comments to assist those who might want to modify or re-use it; this version expands on those comments to explain more about the process of developing the generator and to reflect on the nature of comments and the glossing of code. This file, including comments both practical and reflective, is offered as one model for the criticism of literary works written in code.